MicroRNA Regulation of Cholesterol Metabolism. (10th July 2012) - Rotllan, Noemi; Fernández-Hernando, Carlos
Abstract : Disruption of cellular cholesterol balance results in pathologic processes including atherosclerosis, metabolic syndrome, type II diabetes and Alzheimer's disease. Maintenance of cholesterol homeostasis requires constant metabolic adjustment, achieved partly through the fine regulation of the classical transcription factors (e.g., by SREBP and LXR), but also through members of a class of noncoding RNAs termed miRNAs. Some miRNAs have now been identified to be potent post-transcriptional regulators of lipid metabolism genes, including miR-122, miR-33, miR-758, and miR-106b. Different strategies have been developed to modulate miRNA effects for therapeutic purposes. The promise demonstrated by the use of anti-miRs in human preclinical studies, in the case of miR-122, raises the possibility that miR-33, miR-758, and miR-106b may become viable therapeutic targets in future. This review summarizes the evidence for a critical role of some miRNAs in regulating cholesterol metabolism and suggests novel ways to manage dyslipidemias and cardiovascular diseases.